Studies on Schismatoglottideae (Araceae) of Borneo LI: Ooia revised, including a reconsideration of Ooia grabowskii - Wong, Sin Yeng; Boyce, P.C (The Journal of Japanese Botany, 2016)
Recollection of Ooia grabowskii at the Type locality in Kalimantan Selatan, Indonesian Borneo, has revealed the name to have been comprehensively misapplied to five taxonomically new Bornean Ooia species, here described as: Ooia altar S. Y. Wong & P. C. Boyce, sp. nov., O. basalticola S. Y. Wong & P. C. Boyce, sp. nov., O. glans S. Y. Wong & P. C. Boyce, sp. nov., O. secta S. Y. Wong & P. C. Boyce, sp. nov., and O. suavis S. Y. Wong & P. C. Boyce, sp. nov. Ooia grabowskii is endemic to the southern portion of the Meratus Mountains, Kalimantan Selatan. Clarification of O. grabowskii additionally reveals that Rhynchopyle havilandii Engl. [≡ Piptospatha havilandii (Engl.) Engl.; Schismatoglottis havilandii (Engl.) M. Hotta], until now treated as a heterotypic synonym of O. grabowskii, to be a distinct species of Ooia: the combination Ooia havilandii (Engl.) S. Y. Wong & P. C. Boyce, comb. nov. is made. Newly observed spathe senescence mechanics of O. grabowskii and O. basalticola are strikingly in agreement with those of Piptospatha manduensis Bogner & A. Hay. Combined with the highly atypical (for Piptospatha) fragrant inflorescences, pubescent staminate flowers, and deciduous non-pistillate flowers, and typical (for Ooia) creeping/rooting stems and pendulous infructescences occurring in P. manuduensis prompts removal of P. manduensis from Piptospatha and incorporation into Ooia – the combination Ooia manduensis (Bogner & A. Hay) S. Y. Wong & P. C. Boyce, comb. nov. is made. These novelties and transfers, taken together with pre-existing species, brings Ooia to 10 species. All species are illustrated from living plants, with Ooia grabowskii additionally figured from the Berlin Holotype, and from Engler’s Araceae Exsiccatae et Illustratae No. 196. An identification key to all described Ooia species is provided.